Nudging users towards cross-border mediation: Is it really about harmonised enforcement regulation? - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2014)
In this paper the author challenges her audience to think in different ways about creating the shift needed to make cross-border mediation practice a reality rather than rhetoric. Within Asia, Hong Kong, Singapore and other centres are positioning themselves as regional leaders in cross-border mediation. Statistically though, there is not an enormous amount of cross-border mediation going on. Despite the apparent advantages of mediation and the international regulatory activity outlined above, cross-border commercial mediation practice has been slow to develop. At dispute resolution conferences and other get-togethers, mediators and other ADR advocates ask themselves, “Why”? While there is little empirical data to suggest why this is the case, numerous writers offer explanations along the following lines. Users are said to remain cautious about mediation’s effectiveness in the absence of a mature and comprehensive international legal framework to regulate the rights and obligations of mediation participants such as those relating to the enforceability of MSAs. In particular, diversity of enforcement mechanisms for cross-border MSAs is seen as a major obstacle to the development of global mediation practice.